"The Group Knobe Effect": evidence that people intuitively attribute agency and responsibility to groups. (2nd January 2019) - Michael, John Andrew; Szigeti, András
Abstract : In the current paper, we present and discuss a series of experiments in which we investigated people's willingness to ascribe intentions, as well as blame and praise, to groups. The experiments draw upon the so-called "Knobe Effect". Knobe [2003. "Intentional action and side effects in ordinary language." Analysis 63: 190–194] found that the positiveness or negativeness of side-effects of actions influences people's assessment of whether those side-effects were brought about intentionally, and also that people are more willing to assign blame for negative side-effects of actions than they are to assign praise for positive side-effect of actions. Building upon this research, we found evidence that the positiveness or negativeness of side-effects of group actions influences people's willingness to attribute intentions to groups (Experiment 1a), and that people are more willing to assign blame to groups for negative side-effects of actions than they are to assign praise to groups for positive side-effects of actions (Experiment 1b). We also found evidence (Experiments 2a, 2b, 3 and 4) that the "Group Knobe Effect" persists even when intentions and blame/praise are attributed to groups non-distributively, indicating that people tend not to think of group intentions and group blame/praise in distributive terms. We conclude that the folk are collectivist about group intentions, and also about the blameworthiness and praiseworthiness of groups.